Enhancing Bilingual Literacy and Tawhid Values through Digital Islamic Parenting Workshops for Early Childhood Educators - Dian Anggraini; Kholida Nur; Yuning Eka Rahma Wati (CV Yazri Aksara Nusantara, 2025)
This community service program aimed to strengthen the integration of tauhid-based values within bilingual digital pedagogy for teachers in Early Childhood Education (ECE). The initiative was developed in response to the increasing linguistic and technological demands placed on Islamic educators, alongside the persistent fragmentation between language instruction and spiritual formation. Utilizing the Participatory Action Research (PAR) approach, the program engaged teachers in iterative cycles of collaborative planning, action, reflection, and refinement, enabling them to construct learning experiences that embed English and Arabic vocabulary within tauhid-oriented meaning-making. The results indicated substantial improvements in teachers’ pedagogical competence, conceptual understanding, and technological proficiency, evidenced by their ability to design and produce digital Islamic learning media such as e-posters, multimedia storytelling, and interactive vocabulary tools. Furthermore, the workshop fostered stronger partnerships between teachers and parents, leading to a unified educational ecosystem grounded in shared spiritual responsibility. The findings validate that bilingual literacy, when anchored in Islamic theology, functions not merely as a communicative skill but as an instrument of identity building and moral cultivation. The program demonstrates a scalable and contextually relevant model for Islamic early childhood pedagogy, offering a transformative direction for future curriculum development, institutional collaboration, and long-term educational reform.